Relationship between rural land titling and land transfer in China: a systematic literature review and meta-analysis - Xie, Lin; Zhang, Juan; Huang, Wenyi; Ke, Doudou; Li, Linna (Frontiers in Sustainable Food Systems, 2023)
The traditional land system of rural communities in China has been an obstacle to the sustainable development of land transfer. To facilitate a more efficient allocation of resources, the Chinese government has implemented the largest rural land titling action in the world. However, there has been much debate in scholarly circles regarding the correlation between rural land titling and rural land transactions. By employing meta-analysis technology, this paper evaluates the relationship between rural land titling and rural land transactions. According to the meta-analysis results, rural land titling is only a minor contributor to rural land transfer; it only contributes to rural land transfer-out, with no effect on rural land transfer-in. Furthermore, education, age, labor force, agricultural fixed assets owned, area of contracted rural land, and publication time were identified as situational variables that affect the relationship between rural land titling and rural land transfer-out. This research provides insight into how to promote the sustainable development of agricultural land economy by promoting land transfer, as well as further topics for future study.